2017
DOI: 10.3892/ijmm.2017.3163
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid induces apoptosis by regulating PI3K/Akt signaling and mitochondrial pathways in human cervical cancer cells

Abstract: Betulinic acid (BA), a potential anticancer compound, could induce apoptosis in human cervical cancer (HeLa) cells, but its mechanism has yet to be fully elucidated. The present study was focused on deciphering the detailed molecular mechanism of BA-induced apoptosis. In the present study, results indicated that BA was highly effective against HeLa cells via induction of time-dependent apoptosis, and the authors demonstrated that the BA treatment acted through downregulating a phosphatidylinositol 3-kinase (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 36 publications
6
68
2
2
Order By: Relevance
“…The results of this work showed that BA supplementation reversed the ratios of p-JAK2/JAK2, p-STAT3/STAT3, and Bax/Bcl-2, and reduced the activation of caspase-3, which was confirmed by the TUNEL results; these data suggest that T-2-toxin-induced apoptosis was blocked by BA treatment. Accumulating evidence has demonstrated that BA is able to induce apoptosis in a broad variety of cell types, including human cervical cancer cells, breast cancer cells, and HT-29 colorectal cancer cells [41][42][43]. In our experiment, BA acted as an antiapoptotic agent in the testes of mice treated with T-2 toxin.…”
Section: Discussionmentioning
confidence: 52%
“…The results of this work showed that BA supplementation reversed the ratios of p-JAK2/JAK2, p-STAT3/STAT3, and Bax/Bcl-2, and reduced the activation of caspase-3, which was confirmed by the TUNEL results; these data suggest that T-2-toxin-induced apoptosis was blocked by BA treatment. Accumulating evidence has demonstrated that BA is able to induce apoptosis in a broad variety of cell types, including human cervical cancer cells, breast cancer cells, and HT-29 colorectal cancer cells [41][42][43]. In our experiment, BA acted as an antiapoptotic agent in the testes of mice treated with T-2 toxin.…”
Section: Discussionmentioning
confidence: 52%
“…MicroRNAs (miRNAs) are short noncoding RNAs molecules (19)(20)(21)(22)(23)(24)(25) nucleotides length) that regulate the expression of many human-protein-coding genes. 8 miRNA plays an important role in a variety of biological processes by bind to the complementary sequences in the 3ʹ untranslated region to involve the post-transcriptional regulation.…”
Section: Introductionmentioning
confidence: 99%
“…18 Growth factors and hormones trigger PI3K phosphorylation events, which in turn coordinate cell growth, cell cycle entry, cell migration and cell survival. 19 Moreover, the PI3K pathway inhibits the cell cycle progression by repressing downstream molecule Akt. 19 These findings together build a strong rationale for the miR-34a and PI3K/AKT pathway in order to achieve a better outcome for osteoarthritis patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BA is attracting increasing attention due to its high selectivity for cancer cells, with no apparent systemic toxicity in mice [10,11]. BA proapoptotic effects in malignant cells have been traditionally linked to mitochondrial ROS generation and induction of DNA damage [12,13]; however, Y. Zheng et al revealed that BA attenuated migration and invasion of highly aggressive breast cancer cells via aerobic glycolysis inhibition, and glucose-regulated protein (GRP78), a major chaperone in the endoplasmic reticulum, was found to be critical for inhibitory effects of BA on glycolytic proteins. Moreover, Y. Zheng et al's findings indicated that the oxygen consumption rate (OCR) of breast cancer cell lines MDA-MB-231 and BT-549 decreased following BA treatment, thus suggesting that BA switched the cells from an energetic metabolic state to a relatively quiescent state.…”
mentioning
confidence: 99%